Construction of a mathematical model of an impact device with a two-element striker - Slidenko, Viktor; Slidenko, Oleksandr; Listovschik, Leonid; Novykov, Anton; But, Viacheslav (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the oscillation process of an impact device with a two-element striker, which makes it possible to increase the efficiency of rock destruction and reduce the recoil on the device body. The task addressed was the construction of a mathematical model that describes the dynamic interaction between the striker elements and the tool while taking into account the resistance of the working medium and impulse loads on the device elements. In the given model, the tool is represented by a rod of variable cross-section, and the striker is represented by two discrete elements with reduced masses. The impact interaction is modeled by the presence of rigid and dissipative links and is described by a system of differential equations with initial and boundary conditions. To solve the initial boundary value problem, a numerical method has been used; the parameters of the method are determined by solving the model problem, which is constructed for a discrete model with three discrete masses. An increase in the co-impact time relative to a device with a solid striker by 1.5...2 times to values of 350...500 μs was established. With a load force of 50 to 500 kN in the time range of 0...1 ms and element speeds of 1...8 m/s, the normal stresses in the tool cross-sections were 200...380 MPa. The combination of discrete and continuous elements in the model made it possible to refine the numerical method, taking into account the essential properties inherent in the impulse interaction of the striker elements with the tool and the transfer of impact energy to the processing environment. The model built can be used in the design of impactors with optimal parameters for assessing the shape and duration of the shock pulse, in mining, construction, and oil production